PENGARUH VARIASI KEMIRINGAN DAN PENUTUP LAHAN (LAND COVER) TERHADAP DEBIT ALIRAN PERMUKAAN MENGGUNAKAN RAINFALL SIMULATOR - Khairunnisa, Audrey Vinny; Yuono, Agus Lestari; Sarino, Sarino (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2017)
The increment of urban infrastructure development causes the green land as a catchment area changes into watertight land cover, so the surface runoff increases. When the surface runoff more than the infiltration, its causes floods. One of the solutions is reduce the quantity of watertight land by using the eco-friendly land cover. Besides land cover, land slope is one of the factors affecting amount of surface flow. Therefore, this study was conducted to determine the effect of land cover use and slope relation to surface flow discharge with rain intensity 70 mm / hour. This research was conducted in laboratory using rainfall simulator with area 2 x 1 m and slope variation 0%, 1%, 2%, 3%. Types of land cover used in this research are paving block (stretcher and basketwave pattern), grass block, grass (Pennisetum purpureum schamach), concrete pavement and sand (as land without cover). The results of this study indicate the use of concrete pavement to produce surface flow discharge value ranged from 2.66 to 3.22 liters / minute, paving block of stretcherbond ranged from 2.43 to 3.0 liters / minute, paving block basketwave ranged from 2.17 to 2.72 liters / minute, grass block ranged from 1.99 to 2.59 liters / minute. Grass produced surface flow discharge ranging from 1.40 to 2.12 liters / minute and sand as land without cover ranged from 1.48 to 2.29 liters / minute. The land slope variation is very influential on the amount of surface runoff discharge. The steeper land, make the surface runoff discharge increase.